Piezo1 channels mediate vasorelaxation of uterine arteries from pseudopregnant rats - Arishe, Olufunke O.; McKenzie, Jaine; Dela Justina, Vanessa; Dos Anjos Moraes, Raiana; Webb, R. Clinton; Priviero, Fernanda (Frontiers in Physiology, 2023)
Introduction: There is a great increase in uterine arterial blood flow during normal pregnancy, which is a result of the cardiovascular changes that occur in pregnancy to adapt the maternal vascular system to meet the increased metabolic needs of both the mother and the fetus. The cardiovascular changes include an increase in cardiac output and more importantly, dilation of the maternal uterine arteries. However, the exact mechanism for the vasodilation is not fully known. Piezo1 mechanosensitive channels are highly expressed in endothelial and vascular smooth muscle cells of small-diameter arteries and play a role in structural remodeling. In this study, we hypothesize that the mechanosensitive Piezo1 channel plays a role in the dilation of the uterine artery (UA) during pregnancy. Methods: For this, 14-week-old pseudopregnant and virgin Sprague Dawley rats were used. In isolated segments of UA and mesenteric resistance arteries (MRA) mounted in a wire myograph, we investigated the effects of chemical activation of Piezo1, using Yoda1. The mechanism of Yoda1 induced relaxation was assessed by incubating the vessels with either vehicle or one of the following inhibitors: the nitric oxide synthase inhibitor (L-NAME, 10-4M), the cyclooxygenase (COX) 1 and 2 inhibitor (indomethacin, 10-5 M), the non-selective potassium channel inhibitor, tetraethylammonium (TEA, 2 x10-3 M), blocker of the intermediate conductance Ca2+ activated K+ channel (IKCa) (charybdotoxin, ChTX, 10-10 M), inhibitor of the small conductance Ca2+ activated K+ channel (SKCa) apamin (Ap, 10-9 M); and in the presence of a potassium-free physiological salt solution. (K+-free PSS). Results: Our results show that concentration-dependent relaxation responses to Yoda1 are greater in the UA of the pseudo-pregnant rats than in those from the virgin rats while no differences between groups was observed in the MRAs. In both vascular beds, either in virgin or in pseudopregnant, relaxation to Yoda1 was at least in part nitric oxide- dependent. Conclusion: In conclusion, Piezo1 channel mediates nitric oxide-dependent relaxation and this channel seems to contribute to the greater dilation that occurs in the uterine arteries of pseudo-pregnant rats.